Computerized neuropsychological assessment devices in multiple sclerosis: A systematic review. (December 2019) - Wojcik, Curtis M; Beier, Meghan; Costello, Kathleen; DeLuca, John; Feinstein, Anthony; Goverover, Yael; Gudesblatt, Mark; Jaworski, Michael; Kalb, Rosalind; Kostich, Lori; LaRocca, Nicholas G; Rodgers, Jonathan D; et al.
Background: The proliferation of computerized neuropsychological assessment devices (CNADs) for screening and monitoring cognitive impairment is increasing exponentially. Previous reviews of computerized tests for multiple sclerosis (MS) were primarily qualitative and did not rigorously compare CNADs on psychometric properties. Objective: We aimed to systematically review the literature on the use of CNADs in MS and identify test batteries and single tests with good evidence for reliability and validity. Method: A search of four major online databases was conducted for publications related to computerized testing and MS. Test–retest reliability and validity coefficients and effect sizes were recorded for each CNAD test, along with administration characteristics. Results: We identified 11 batteries and 33 individual tests from 120 peer-reviewed articles meeting the inclusion criteria. CNADs with the strongest psychometric support include the CogState Brief Battery, Cognitive Drug Research Battery, NeuroTrax, CNS-Vital Signs, and computer-based administrations of the Symbol Digit Modalities Test. Conclusion: We identified several CNADs that are valid to screen for MS-related cognitive impairment, or to supplement full, conventional neuropsychological assessment. The necessity of testing with a technician, and in a controlled clinic/laboratory environment, remains uncertain.